Kekuatan Pembuktian Surat di Bawah Tangan yang Telah Didaftarkan pada Buku Khusus oleh Notaris (Studi Putusan Nomor 29/Pdt.G./2019/PN Pya) - Fahriza Hafiz; tony; hasim purba (Jurnal Hukum Lex Generalis, 2025)
The registration of private deeds in legal context is the recording of underhand documents by a notary in a special register to provide legal certainty regarding their existence and date, without converting them into authentic deeds. This normative legal research analyzes the legal status and evidentiary strength of registered private deeds, examining Court Decision No. 29/Pdt.G./2019/PN.Pya. Using secondary data from legal documents and regulations, the study finds that registration under the Notarial Law provides administrative formality and legal protection. However, registered private deeds retain their original nature, with probative value depending on signatories' acknowledgment. Notaries are responsible for procedural accuracy but not content validity.